The memory of the portuguese First Republic throughout the twentieth century - Sardica, José Miguel (2011)
The Portuguese First Republic (1910-1926) is still today a historical period marked by the controversies it generated. Despite its overall failure as an attempt to democratize and modernize the country, the regime left a powerful legacy in the collective memory, acritically glorified or condemned, depending on whether it fueled the apologetic and proselytic view of the utopia-to-be or, in contrast, the devilish view of a close-to-anarchy and Jacobin-like experience. This text analyzes the way in which the First Republic’s memory became a topic for heated debate, marking out positions and projecting them onto the appreciations that successive Portuguese generations were to make on this matter throughout the twentieth century.